Mechanism study of natural gas pre-ignition induced by the auto-ignition of lubricating oil. (1st May 2022) - Gong, Zhen; Hu, Mingda; Fang, Yuan; Zhang, Dong; Feng, Liyan
Highlights: Occurrence mechanisms of abnormal combustion were revealed by RCM. The influence of ambient gas on abnormal combustion is the strongest. The influence of thermal conditions on abnormal combustion is the second strongest. The influence of oil droplet properties on abnormal combustion is the weakest. The suppressing methods of abnormal combustion were obtained. Abstract: The lubricating oil auto-ignition induced pre-ignition (LOAP) is the most threatening abnormal combustion in natural gas engines. To reveal the mechanisms of the occurrence and the suppressing methods of abnormal combustion in natural gas/diesel marine engines, influence mechanisms of thermodynamic condition, reagent gas composition and the volume of oil droplet on abnormal combustion were investigated by a newly developed visual rapid compression machine (RCM). Experimental results indicate that the auto-ignition of in-cylinder suspended oil droplet can cause the fuel–air pre-ignition. Furthermore, the heated burning residuals of oil droplet can glow to become the ignition source which can induce the pre-ignition. Two factors, total combustion duration and maximum pressure rise rate (PRRmax ), are introduced. Shorter total combustion duration and higher PRRmax represent a stronger occurrence tendency of LOAP in the dual-fuel engine. Under the range of reagent gas composition and thermodynamic condition in the dual-fuel engine, rising equivalence ratio ( ϕ ) and reducing methane number (MN) of natural gas can reduce the total combustion duration by 57% and 41% respectively, and increase PRRmax by about 30 times and 1.9 times. Rising compression temperature and pressure shortens the total combustion duration by 40.7% and 40.1% respectively and increases PRRmax by about 1.3 times and 0.8 times. Reducing oil droplet volume only slightly advances its ignition moment, and has little effect on subsequent natural gas pre-ignition. Based on the result, the most influential factors on the promotion extent of pre-ignition are ranked as: ϕ, MN, temperature, pressure, droplet volume (strongest: reagent gases, moderate: thermodynamic conditions, weakest: droplet volume). Therefore, to prevent the occurrence of LOAP, the existence of in-cylinder local rich natural gas region should be avoided first. Then the high-MN natural gas ought to be applied. The compression temperature and pressure need to be reduced moderately on the premise of ensuring thermal efficiency. Moreover, the small volume oil mist should be avoided to enter into cylinder by optimizing oil injection strategies and scavenging port structures. These findings are beneficial to prevent abnormal combustions and further improve engine power performance.